Designing and implementing a STEM career maturity program for prospective counselors - Engin Karahan; Ahmet Kara; Ahmet Oğuz Akçay (SpringerOpen, 2021)
Abstract Background Although the importance of directing students to career options in Science, Technology, Engineering, and Mathematics (STEM) fields at early ages has been emphasized in the literature, it has not been clearly stated just who will play a role in this process and what kind of consultancy process will be followed. It is of great importance for prospective counselors, who are studying in the field of counseling, to master the career selection process, specifically for STEM, towards achieving the national goals. Therefore, the purpose of this study was to investigate the career counseling competencies of prospective counselors who were participating in a STEM career maturity program. Findings The current study employed the mixed-methods sequential explanatory design. In this design, after collecting and analyzing the quantitative and qualitative data, both datasets were then interpreted together. The quantitative data analysis revealed a significant difference between the post-test mean career counseling and performance indicator scores of the experimental and the control groups (u = 49.00; P < 0.05). The career counseling and performance indicator mean rank and sum of mean scores of the students in the experimental group were higher than those of the students in the control group. The mean career counseling and performance indicator scores of the students in the experimental group increased after the experimental application (Z = - 3.07; P < 0.01). Moreover, the effect size was also calculated and determined to be 0.58. As a result of the analysis of qualitative data, 4 themes were established, comprising (1) personal and professional development, (2) awareness of the STEM majors and careers, (3) STEM-focused career counseling, and (4) feedback about the program. Conclusions This study found that the STEM career maturity program that was designed and implemented herein resulted in positive impacts on the career counseling competencies and performance indicators of the participants, as well as their knowledge and awareness of professional STEM areas. Considering the role of school counselors in supporting students in choosing STEM careers, this newly proposed STEM career maturity program will provide a strong model for supporting pre-service and in-service school counselors in directing students towards STEM fields, so as to develop a qualified workforce in STEM fields, which is one of the main objectives of the STEM education reform.